Multisystem inflammatory syndrome associated with COVID-19 in pediatric patients - Fernández, Gerardo (2022)
Pediatric Multisystem Inflammatory Syndrome (P-MIS) linked to SARS-CoV-2 is a generalized inflammatory reaction that develops approximately 4-6 weeks after COVID-19 illness. The aim of the article was to analyze the immunopathogenesis, diagnosis and treatment of P-MIS. A systematic literature review was performed using databases such as Embase, Redalyc, LILACS, SciELO, Springer, Elsevier, EBSCO and Google Scholar and the keywords: Coronavirus disease, Kawasaki disease, child, intravenous immunoglobulins. Inclusion criteria were: full articles, published between the years 2019-2022, in English and Spanish. Of the 273 articles found, 243 articles were rejected for not meeting the established criteria, with 30 articles selected as eligible. According to the results, SIM-P is characterized by fever, myocardial injury, shock and development of coronary artery aneurysms; laboratory tests show: elevation of markers of inflammation, changes in coagulation tests, especially significant elevation of D-dimer and fibrinogen and elevation of markers of myocardial injury, troponin and natriuretic peptide. Phase 1 treatment occurs with the administration of intravenous immunoglobulin G (IVIG), corticosteroids, low molecular weight heparin in a prophylactic dose; in phase 2, treatment consists of administration of a second dose of IVIG, progressive reduction of prednisone and use of biological therapy; and, in phase 3, infliximab or tocilizumab is used. In conclusion, SIM-P has elevated inflammatory markers and multi-organ involvement, with no associated bacterial diagnosis, with evidence of infection or recent exposure to SARS-CoV-2.